1997
DOI: 10.1016/s0194-59989770307-3
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Hearing Loss in Sickle Cell Disease: A Case Report

Abstract: S i c k l e cell disease (SCD) is an inherited hematologic disorder that may involve sensorineural hearing loss (SNHL) and that is common in those of African descent. It is an autosomal recessive hemoglobinopathy in which the carrier is said to have sickle cell trait. In African-Americans the prevalence of sickle cell trait is 7% to 9%, and that of SCD is approximately 0.25%. 1,2 Conventions of nomenclature define SCD as the family of hemoglobinopathies, including the homozygous form, sickle cell anemia (Hb SS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…Our data emphasized the need for individuals presenting with SSNHL, especially women of reproductive age with a history of vascular thrombosis and/or pregnancy loss, to be tested for anti-β-2-glycoprotein-1 antibodies, lupus anticoagulant, and anti-cardiolipin antibodies; this recommendation stems from the potential role of antiphospholipid syndrome in the pathogenesis of SSNHL, as a consequence of microthrombus formation in the labyrinthine vasculature [ 42 , 43 ]. The present study also confirmed that sickle cell disease, a genetic disorder characterized by abnormal hemoglobin production, is another possible cause of SSNHL in individuals younger than 40 years of age [ 44 , 45 ]. Indeed, these patients have sickle-shaped red blood cells that can obstruct small blood vessels in the inner ear, leading to ischemia and subsequent SSNHL; in addition, the breakdown of sickle cells releases hemoglobin, which can be toxic to the cochlear structures [ 46 ].…”
Section: Discussionsupporting
confidence: 85%
“…Our data emphasized the need for individuals presenting with SSNHL, especially women of reproductive age with a history of vascular thrombosis and/or pregnancy loss, to be tested for anti-β-2-glycoprotein-1 antibodies, lupus anticoagulant, and anti-cardiolipin antibodies; this recommendation stems from the potential role of antiphospholipid syndrome in the pathogenesis of SSNHL, as a consequence of microthrombus formation in the labyrinthine vasculature [ 42 , 43 ]. The present study also confirmed that sickle cell disease, a genetic disorder characterized by abnormal hemoglobin production, is another possible cause of SSNHL in individuals younger than 40 years of age [ 44 , 45 ]. Indeed, these patients have sickle-shaped red blood cells that can obstruct small blood vessels in the inner ear, leading to ischemia and subsequent SSNHL; in addition, the breakdown of sickle cells releases hemoglobin, which can be toxic to the cochlear structures [ 46 ].…”
Section: Discussionsupporting
confidence: 85%